Microwave Assisted Synthesis and Characterization of Semicarbazones - Jadon, Sudha; M. Khedr, Abdalla; Kumar, Sanjeev; Yadav, Sneha; Kumar, Vipin; C. Gupta, Kishan (Asian Journal of Chemistry, 2011)
An efficient and simple microwave assisted procedure has been developed for conversion of substituted aryl aldehyde to corresponding semicarbazone by reaction with semicarbazide hydrochloride in presence of sodium acetate. The synthesized semicarbazones have been characterized by physico-chemical and spectral data.